Space averaging in parabolic equations - Kulinich , G. L.; Mynbaeva , M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We find an explicit formula for the limit of a solution of the Cauchy problem, when space averages of coefficients of a parabolic second order partial differential equation of a special type exist.